Distinct behavior of bovine-associated staphylococci species in their ability to resist phagocytosis and trigger respiratory burst activity by blood and milk polymorphonuclear leukocytes in dairy cows - Rodrigo M. Souza; Fernando N. Souza; Camila F. Batista; Sofie Piepers; Anneleen De Visscher; Kamila R. Santos; Paula C. Molinari; José A. Ferronatto; Adriano Franca da Cunha; Maiara G. Blagitz; Guilherme G. da Silva; Francisco P. Rennó; et al. (Journal of Dairy Science, 2022)
ABSTRACT: Mastitis affects a high proportion of dairy cows and is still one of the greatest challenges faced by the dairy industry. Staphylococcal bacteria remain the most important cause of mastitis worldwide. We investigated how distinct staphylococcal species evade some critical host defense mechanisms, which may dictate the establishment, severity, and persistence of infection and the outcome of possible therapeutic and prevention interventions. Thus, the present study investigated variations among distinct bovine-associated staphylococci in their capability to resist phagocytosis and to trigger respiratory burst activity of blood and milk polymorphonuclear neutrophil leukocytes (PMNL) in dairy cows. To do so, PMNL of 6 primiparous and 6 multiparous dairy cows were used. A collection of 38 non-aureus staphylococci (NAS) and 12 Staphylococcus aureus were included. The phagocytosis and intracellular reactive oxygen species (ROS) production by blood and milk PMNL were analyzed by flow cytometry. Phagocytosis, by both blood and milk PMNL, did not differ between S. aureus and NAS as a group, although within-NAS species differences were observed. Staphylococcus chromogenes (a so-called milk-adapted NAS species) better resisted phagocytosis by blood PMNL than the so-called environmental (i.e., Staphylococcus fleurettii) and opportunistic (i.e., Staphylococcus haemolyticus) NAS species. Otherwise, S. haemolyticus was better phagocytosed by blood PMNL than S. aureus, S. fleurettii, and S. chromogenes. No influence of the origin of the isolates within the staphylococci species in the resistance to phagocytosis by blood and milk PMNL was found. Overall, both S. aureus and NAS did not inhibit intracellular ROS production in blood and milk PMNL. Non-aureus staphylococci induced fewer ROS by milk PMNL than S. aureus, which was not true for blood PMNL, although species-specific differences in the intensity of ROS production were observed. Staphylococcus chromogenes induced more blood PMNL ROS than S. fleurettii and S. haemolyticus, and as much as S. aureus. Conversely, S. chromogenes induced fewer milk PMNL ROS than S. aureus. The origin of the isolates within the staphylococci species did not affect the ROS production by blood and milk PMNL. In conclusion, our study showed differences in staphylococci species in evading phagocytosis and triggering ROS production, which may explain the ability of some staphylococci species (i.e., S. aureus and S. chromogenes) to cause persistent infection and induce inflammation.